Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Guru dengan Moderasi Supervisi Akademik pada Guru Smk Swasta - Muslikin, Muslikin; Srimindarti, Ceacilia (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
The purpose of this study was to determine the effect of work discipline and work motivation on teacher performance with academic supervision moderation on private vocational high school teachers in Mijen District, Semarang City. This type of research is explanatory research. The results of the study, Work discipline, has a coefficient of 0.298 with a t value of 2.624 and a significance of 0.010. This shows that work discipline has a significant positive effect on teacher performance. Work Motivation, has a coefficient of 0.269 with a t value of 4.483 and a significance of 0.000. This shows that work motivation also has a very significant positive effect on teacher performance. Academic Supervision does not moderate the effect of work discipline and is not significant on teacher performance, and Academic supervision moderates the effect of work motivation and has a positive and significant effect on teacher performance. Conclusion, work discipline and work motivation have a positive effect on teacher performance, while academic supervision is not a moderating factor that influences work discipline and motivation on teacher performance.   Keywords: Work Discipline, Teacher Performance, Academic Supervision Moderation, Work Motivation